Հայաստանի ճարտարապետության պատմության հիմնովին վերանայման խնդիրը - Վահագն Գրիգորյան (ՀՀ ԳԱԱ հրատ.)
Представляя армянскую архитектуру с IV в. до н. э. по VII в. н. э., исследователи взяли за основу две позиции: первая –на пороге провозглашения христианства государственной религией Армении все языческие памятники, за исключением храма в Гарни, беспощадно были уничтожены; вторая–строительство христианских храмов, а именно, архитектура развивалась шаг за шагом, этап за этапом, от простых до более сложных композиций, параллельно со становлением богослужения в армянской церкви и разработкой его требований. To present the Armenian architecture of the 4th century B.C. up to the 7th century A.D., the researchers have taken two viewpoints as a starting point and basis: firstly, on the threshold of adopting Christianity as state religion, all pagan cultic structures (except the temple of Garni) were mercilessly destroyed; secondly, parallel to the development of the requirements of Armenian liturgy, the Christian temple-building, i.e. architecture, evolved step by step and phase by phase, i.e. along the way of creating compositions from simple to more complex ones.
Keywords: N Fine Arts; NA Architecture